Impact of cropping methods on biodiversity in coffee agroecosystems in Sumatra, Indonesia - Gillison, A.N.; Liswanti, N.; Budidarsono, S.; Noordwijk, Meine van; Tomich, Thomas P. (2004)
The sustainable management of biodiversity and productivity in forested lands requires an understanding of key interactions between socioeconomic and biophysical factors and their response to environmental change. Appropriate baseline data are rarely available. As part of a broader study on biodiversity and profitability, we examined the impact of different cropping methods on biodiversity (plant species richness) along a subjectively determined land-use intensity gradient in southern Sumatra, ranging from primary and secondary forest to coffee-farming systems (simple, complex, with and without shade crops) and smallholder coffee plantings, at increasing levels of intensity. We used 24 (40 x 5 m) plots to record site physical data, including soil nutrients and soil texture together with vegetation structure, all vascular plant species, and plant functional types (PFTs—readily observable, adaptive, morphological features). Biodiversity was lowest under simple, intensive, non-shaded farming systems and increased progressively through shaded and more complex agroforests to late secondary and closed-canopy forests. The most efficient single indicators of biodiversity and soil nutrient status were PFT richness and a derived measure of plant functional complexity. Vegetation structure, tree dry weight, and duration of the land-use type, to a lesser degree, were also highly correlated with biodiversity. Together with a vegetation, or V index, the close correspondence between these variables and soil nutrients suggests they are potentially useful indicators of coffee production and profitability across different farming systems. These findings provide a unique quantitative basis for a subsequent study of the nexus between biodiversity and profitability.